Defining and building a Decision Support System: the Experience of the Bibliothèque Nnationale de France - Jouguelet, Suzanne; Pardé, Thierry (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
The Bibliothèque nationale de France (BnF) has chosen to adopt a decision support system. This paper presents the context of this choice and its goals. Secondly, it describes the process, from the needs analysis to the choice of pilot projects, covering two topics: preservation and human resources. We define a decision support system as a set of organized data, tools and reports which provide the means to manage and plan the different activities of an institution.